Reframing Environmental Accounting Through Indigenous-Based Asset Valuation and Socio-Ecological Integration - Kurniawan Patma; Maria Yosephine Dwi Hayu Agustini; Ignasius Dwi Atmana Sutapa (AIBPM Publisher, 2026)
Conventional environmental accounting practices still have significant limitations because they mainly emphasize monetary valuation while neglecting the socio-cultural and ecological dimensions embedded in indigenous asset systems. This research aims to develop an indigenous-based asset valuation and environmental accounting model that integrates economic, ecological, and socio-cultural values within indigenous community enterprises. This study employs a mixed-methods approach using Participatory Action Research (PAR), combining qualitative techniques (in-depth interviews, participatory observation, and collective reflection) with quantitative valuation based on the Total Economic Value (TEV) framework. The findings reveal that indigenous assets are perceived as collective socio-ecological trusts, where non-use values, especially existence and bequest values, are central alongside direct and indirect use values. The study proposes an indigenous-based environmental accounting model that generates ecological financial statements covering natural resource assets, social and environmental liabilities, and non-financial reports. This model has practical implications for improving accountability, sustainability, and policy formulation in indigenous economic governance, but it is context-specific and requires adaptation for broader application in different indigenous settings.